The Effect of Industrial Specialization Auditors and Audit Committee Expertise on Audit Quality - Kurniasih, Indah; Kiswanto, Kiswanto (Accounting Analysis Journal, 2019)
The purpose of this research is to analyze the impact of auditor industry specialization and audit committee specific expertise, which is divided into accounting, finance, and supervisory expertise, controlled by board of commissioner size, board of director size, firm size, leverage, and profitability. This research uses secondary data with population of 144 manufacturing companies listed on the Indonesian Stock Exchange (IDX) during 2014-2016. The sample selection method was purposive sampling which generates 87 firms as the sample. The data analysis method was multiple linear regression analysis by IBM SPSS version 23.The results showed that the auditor industry specialization and audit committee accounting expertise have positive effect on audit quality. While the audit committee finance and supervisory expertises do not affect the audit quality. Control variables board of commissioner size, firm size, leverage, and profitability affect to audit quality. However, board of director size does not affect to audit quality. The conclusion of this research is auditor industry specialist and audit committee who has accounting expertise are able to improve the audit quality.